Acceptance of pneumococcal vaccination in older adults: A general population-based survey. Issue 47 (16th November 2021) - Huang, Junjie; Bai, Yijun; Ding, Hanyue; Wang, Boyuan; Ngai, Chun Ho; Kwok, Kin-on; Wong, Eliza L.Y.; Wong, Martin C.S.; Yeoh, Eng-Kiong
Abstract: Background: Pneumococcal infection is a leading cause of disability and death globally. The Hong Kong Government has launched two programmes for pneumococcal vaccination - The Vaccination Subsidy Scheme (VSS) and the Government Vaccination Programme (GVP). This study aimed to examine the enabling factors, obstacles and perception of pneumococcal vaccination, and their association with its uptake in a general Chinese population. Methods: We performed a population-based, telephone survey in the general public aged 65 or above via simple random sampling. A validated survey based on the Health Belief Model (HBM) was used. Their socio-demographic information; history of previous participation in the GVP or VSS; and self-perceived health status were captured. Binary logistic regression models were constructed to examine the factors independently associated with vaccination. Results: A total of 1, 000 respondents were enrolled in the study, with 402 (40.2%) respondents having intention to join the GVP/VSS in 12 months. Respondents with long-term medical consultant and medication (adjusted odds ratios [aOR] = 1.541, 95% confidence interval (CI): 1.008–2.356, p = 0.046); high levels of perceived susceptibility of infections (aOR = 3.624, 95 %CI: 2.318–5.665, p < 0.001); high levels of perceived benefits of vaccine (aOR = 1.699, 95 %CI: 1.153–2.504, p < 0.001); recommendations from government (aOR = 8.025, 95 %CI: 4.771–13.497, p < 0.001) or physicians (aOR = 7.399, 95 %CI: 3.472–15.764, p = 0.008); and high levels of self-efficacy (aOR = 3.045, 95 %CI: 1.458–6.362, p = 0.003) were more likely to have intention to participate in the vaccination programme. Conclusions: The acceptance rate of pneumococcal vaccination programme remained suboptimal in the population. The government and physicians should be involved in the promotion of pneumococcal vaccination and GVP/VSS by increasing perceived benefits and self-efficacy, and reducing barriers towards vaccination among the target population. More studies are required to confirm our findings in other settings.